Key success factors for social services organisations in Poland = Kluczowe czynniki sukcesu ośrodków pomocy społecznej w Polsce - Kotas, Maria (Zielona Góra: Faculty of Economics and Management Press)
The basic goal behind any action undertaken in an organization management is the will to achieve success. Key (or critical) success factors are the organization?s resources, competence and qualification that create its competitive advantage on a particular market at a given time, and are able to determine its possible future success. The aim of this article is the analysis of the discrepancies between the factual and perceived key success factors of the social service organizations.
Keywords: kluczowe czynniki sukcesu; pomoc społeczna; ośrodki pomocy społecznej; sukces organizacji; key success factors; social services; social service organisation; organizational success